2013
DOI: 10.1007/s11046-013-9663-y
|View full text |Cite
|
Sign up to set email alerts
|

The Predominance of Alternatively Activated Macrophages Following Challenge with Cell Wall Peptide-Polysaccharide After Prior Infection with Sporothrix schenckii

Abstract: Sporotrichosis is a subcutaneous mycosis that is caused by the dimorphic fungus Sporothrix schenckii. This disease generally occurs within the skin and subcutaneous tissues, causing lesions that can spread through adjacent lymphatic vessels and sometimes leading to systemic diseases in immunocompromised patients. Macrophages are crucial for proper immune responses against a variety of pathogens. Furthermore, macrophages can play different roles in response to different microorganisms and forms of activation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 42 publications
3
16
0
Order By: Relevance
“…Maia et al [43] showed a predominantly Th1 ex vivo cytokine release profile in the initial stages of infection and a Th2 predominance in later stages. Aligned with this, our group has previously shown the occurrence of M1 and M2 macrophages in the initial and late phase of the S. schenckii infection, respectively, matching this cytokine pattern [44]. M1 and M2 macrophages are stimulated by Th1 and Th2 cytokines, respectively [45].…”
Section: Discussionsupporting
confidence: 65%
“…Maia et al [43] showed a predominantly Th1 ex vivo cytokine release profile in the initial stages of infection and a Th2 predominance in later stages. Aligned with this, our group has previously shown the occurrence of M1 and M2 macrophages in the initial and late phase of the S. schenckii infection, respectively, matching this cytokine pattern [44]. M1 and M2 macrophages are stimulated by Th1 and Th2 cytokines, respectively [45].…”
Section: Discussionsupporting
confidence: 65%
“…The highest production of IL-1β, TNF-α, IL-10 and NO was observed in the group infected with 0.10%. A balanced production of the proinflammatory IL-1β, TNF-α and the antinflammatory cytokine IL-10 is estimulated during S. schenckii infection (Alegranci et al ., 2013; Maia et al ., 2016). However, although NO is also stimulated and it has an antifungal effect in vitro against this fungus, it also seems to have an immunosuppressive effect that favors fungal infection (Fernandes et al ., 2008; Gonzalves et al ., 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Early activation of the immune system largely depends on pattern recognition receptors (PRRs), many of which involved in the recognition of fungal pathogens [6,7]. Several studies performed in our lab evidenced a role for different PRRs, including the Toll-like receptors (TLRs) 2 [8] and 4 [9,10] and the NOD-like receptor (NLR) family member NLRP3 [11], as important innate components triggered during the S. schenckii infection.…”
Section: Introductionmentioning
confidence: 89%